Underwater Ambient Noise. Proceedings of a Conference Held at SACLANTCEN on 11-14 May 1982. Volume 2. Unclassified Papers. Part 2 - Bendig, Horst; Van Asselt, Hendrik; Bienvenu, Georges; Nuttall, Albert H.; Wagstaff, R. A.; Fraser, I. A.; Bond, James W.; Groen, Mattheus; Wilson, James H.; Wolf, S. N. (1982)
Contents: PROCESSING TECHNIQUES--A method of estimating the influence of ship's noise on ambient noise measurements; Optimal detection and tracking of acoustical noise sources in a time-varying environment; Influence of background- noise spatial coherence on high-resolution passive method; Performance of three averaging methods for various distributions; Is power averaging the best estimator for undersea acoustic data? MODELLING: DEVELOPMENT AND USE--A parametric examination of some properties of the low-frequency ambient-noise field; Detection models and target-information processing; The prediction of temporal statistics of directional ambient shipping noise; Site and frequency dependence of ambient noise in the north eastern Pacific Ocean; ACOUSTIC PROPAGATION EFFECTS--Site dependence of wind-dominated ambient noise in shallow water; Effects of topographic blockage and ocean boundaries on low-frequency noise fields; The seamount as a noise barrier. See also Volume 2, Part 1, ADA125323 and Volume 1, ADC028982.